New Product Development : PentapeADORA / Nur Syuhada Shobir ... [et al.] - Shobir, Nur Syuhada; Azizan, Nurzarifah Syafawati; Mohamad Asri, Raidatul Auna; Syed Azman, Sharifah Ainul Syazwani; Wan Jahari, Wan Nur Irdiana (2021)
Our team decided to develop a new innovative product that can ease the life of everyone especially students and employees. Our product named PentapeADORA stands for multipurpose pen with correction tape combined all in one set. The main features of the product are it has all three basic colours of pen with correction tape behind it combined in one set. The customer can choose which type of model pen they want, whether ballpoint pen or gel pen that comes with different sizes of either 0.5mm or 0.7mm. With these kinds of choices, the customer can choose their preferred type of pen that comes all in one set of three basic colours and correction tape. Moreover an extra refill correction tape is also included in every package of product. In addition, the pen is also a detachable product where it can be split into two since there are two parts of it. The customer also will feel comfortable to carry it around as it is lightweight. Based on the survey we carried out, we found out the problems people faced by using original pens and correction tape sold in the market nowadays. For people that are a minimalist person, they think that it is annoying to carry all different colours of pen and correction tape everywhere. It is because they will encounter problems such as the pen and correction tape might be lost. Every person must have experienced these kinds of incidents once in their life and it will be annoying to buy again many times. Furthermore, the respondents who are an organized person also think that carrying around all pen correction tape will make their pencil case become too compact and it is also uncomfortable to carry a bigger pencil case. It is also will take time to find the pen or correction tape they wanted to use especially when they are rushing.